2015
DOI: 10.1111/fare.12126
|View full text |Cite
|
Sign up to set email alerts
|

Dedication and Sliding in Emerging Adult Cyclical and Non‐Cyclical Romantic Relationships

Abstract: This study investigates the association between dedication commitment and sliding (moving through relationship transitions without considering the consequences) over 14 weeks for emerging adults in cyclical (partners who have broken up and renewed) and non-cyclical relationships. An autoregressive cross-lagged panel and bivariate latent growth curve analysis were conducted using three waves of data from 220 emerging adults in exclusive dating relationships. Results indicated that dedication and sliding may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 19 publications
3
30
0
Order By: Relevance
“…Research has found that young adults in churning relationships, compared with those in stably together or stably broken-up relationships, report more frequent conflict, lower levels of validation, lower levels of commitment, and higher levels of physical violence and verbal abuse (Halpern-Meekin et al 2013a, b). Other research has found that young adult churners report lower relationship satisfaction, feel less certain about the relationship’s future, and are less dedicated to their partners than their counterparts (Vennum and Johnson 2014; Vennum et al 2014, 2015). Qualitative research has also suggested that on/off relationships are frequently troubled, beset by issues such as conflict and infidelity (Cross-Barnett et al 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Research has found that young adults in churning relationships, compared with those in stably together or stably broken-up relationships, report more frequent conflict, lower levels of validation, lower levels of commitment, and higher levels of physical violence and verbal abuse (Halpern-Meekin et al 2013a, b). Other research has found that young adult churners report lower relationship satisfaction, feel less certain about the relationship’s future, and are less dedicated to their partners than their counterparts (Vennum and Johnson 2014; Vennum et al 2014, 2015). Qualitative research has also suggested that on/off relationships are frequently troubled, beset by issues such as conflict and infidelity (Cross-Barnett et al 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Further, fluctuation in perceived partner commitment was related to less uncertainty and turbulence as well; hence, on–off partners are not viewing the fluctuations as making their relationship turbulent and unpredictable but rather as more steady and viable. It is worth noting too that the differences between noncyclical and on–off partners is more pronounced at low levels of fluctuations (see Figures and ), and these differences reflect the consistent finding that on–off partners generally report lower relational quality (Dailey et al, ; Dailey, Pfiester, et al, 2009; Halpern‐Meekin et al, , ; Vennum, ; Vennum et al, ). As such, greater fluctuation in perceived partner commitment appears to raise on–off partners' views of their relational stability to be commensurate with noncyclical partners who experience lower fluctuation.…”
Section: Discussionmentioning
confidence: 62%
“…We also did not collect data on whether participants were in a long‐distance relationship, which might be associated with being in an on–off relationship. The proportion of on–off relationships was also relatively low compared to previous research (e.g., Dailey et al, 2010; Dailey, Pfiester, et al, ; Halpern‐Meekin et al, ; Vennum, ), which limited the power of the analyses. Further, as indicated in footnote 1, some participants developed an on–off relationship during the course of their participation, A longitudinal design that followed participants from the beginning of their relationships and for a longer period of time would allow a more sophisticated classification of on–off status.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…According to Stanley and Rhoades (), the process of consciously deciding whether to be in a relationship over other alternatives also helps partners clarify and build their dedication to one another. Although one study found that relationship deciding was not related to dedication 14 weeks later (Vennum & Fincham, ), more recent research using a cross‐lagged model found a bidirectional negative association between emerging adults' sliding and relationship dedication 7 weeks later (Vennum, Hardy, Sibley, & Fincham, ). This bidirectional effect is not surprising; couples who are more dedicated are more likely to want to improve their relationship and make their relationship a priority (Stanley & Markman, ), increasing the likelihood that they would be more involved in thoughtful decision making about the relationship (Vennum et al, ).…”
Section: Relationship Uncertainty and Attachment Loss Anxiety In Devementioning
confidence: 99%